Stabilization and Controlled Release of Curcumin from Temulawak by Spray-Drying Microencapsulation with Composite Wall Materials - Yonata, Diode; Noor Setiawati Ulvie, Yuliana; Soesanto, Edy; Sulistyowati, Enik; Pranata, Boby; Rosidi, Ali (Trends in Sciences, 2024)
Curcumin, is the main bioactive component of temulawak (Curcuma xanthorriza Roxb), which is a native Indonesian herbal plant. Although it has various health benefits, curcumin’s stability and release time are very low, limiting its application. This study aimed to improve curcumin stability through spray-drying microencapsulation using various wall materials, including maltodextrin (MDE), gum Arabic (GAR), whey protein isolate (WPI), and their composites with β-cyclodextrin (βCD). The resulting curcumin microcapsules from temulawak extract had an irregular morphology with a rough surface and grooves, averaging 2 μm in diameter. The stability of curcumin during storage, against heat and various pH conditions increased significantly, especially in microcapsules prepared with composite wall materials. Curcumin release was faster in single wall material microcapsules, while composite wall material microcapsules achieved release times over 120 min. In conclusion, curcumin from temulawak extract can be prepared by spray drying. MDE-βCD composite wall materials are highly recommended because they produce curcumin microcapsules with improved stability and controlled release compared to single wall materials or other composite wall materials. This research can facilitate the utilization of curcumin from temulawak extract in industrial and food applications. HIGHLIGHTS Temulawak (Curcuma xanthorriza Roxb) is a herbal plant native to Indonesia. Curcumin is the primary polyphenol found in temulawak, which has various health benefits for the body. Curcumin has low stability and fast release time, thus limiting its application in the food and pharmaceutical fields. The microencapsulation process by spray drying can be proposed to increase the stability and release time of curcumin by considering the type of wall material used. The stability of curcumin from temulawak extract microcapsules prepared with maltodextrin (MDE) and β-cyclodextrin (βCD) composite wall materials increased significantly during storage, extreme heat conditions and different pH. The release time of the curcumin total prepared with MDE-βCD composite wall materials reached 158 min. GRAPHICAL ABSTRACT